Neurobiological and Neuroimmune Mechanisms Linking Chronic Pain, Sleep Disturbances and Mental Health Disorders - Boris Burnjakovic; Harrison Moy; Aleksandar Sic; Nebojsa Nick Knezevic (International Journal of Molecular Sciences, 2026)
Chronic pain, sleep disturbances, and mental health disorders such as anxiety and depression disorders frequently co-occur, forming a self-reinforcing cycle that impairs daily functioning and quality of life. Chronic pain is driven by peripheral and central sensitization, the latter sustained by reciprocal microglial–astrocytic crosstalk and maladaptive neuroplasticity. Poor sleep amplifies pain through inflammation and circadian disruption. Imbalances in serotonin, dopamine, and norepinephrine, together with limbic alterations and HPA axis dysregulation, contribute to comorbid anxiety and depression. Elevated pro-inflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α), NF-κB-driven neuroinflammation, and mitochondrial oxidative stress serve as key molecular links. Building on previous evidence, this review presents an updated triadic, mechanism-based framework describing the reciprocal reinforcement among chronic pain, sleep disturbances, and anxiety and depressive disorders. Consequently, therapeutic strategies targeting inflammatory cytokines, microglial and astrocytic activation, neurotransmitter imbalance, and psychological dysfunction may help address these shared neuroimmune and neuroplastic mechanisms underlying these interconnected disorders.